Farol Cultural project of Federal Goiano Institute: contributions to an omnilateral formation (Research, Society and Development, 2020)
This paper aims to demonstrate the relevance of projects in educational institutions to the omnilateral formation of individuals. This is a qualitative research, with a case study on the Farol Cultural Project, carried out annually at the Federal Goiano Institute, since 2013. A literature review of the guidelines of professional and technological education was accomplished about the omnilateral formation of the individual and the contributions that cultural incentive projects can corroborate with this formation. The research revealed that professional and technological education has great importance in the contribution of the “reading of the world” of the individual, so that he can be able to elaborate, from his own life experiences, besides incentives and school formation, knowledge that can bring changes in your reality and in society. It was concluded that professional and technological education and projects, such as Farol Cultural, can contribute to an omnilateral formation of individuals.